2015
DOI: 10.1038/nature14884
|View full text |Cite
|
Sign up to set email alerts
|

Crucial HSP70 co-chaperone complex unlocks metazoan protein disaggregation

Abstract: Protein aggregates are the hallmark of stressed and ageing cells, and characterize several pathophysiological states1,2. Healthy metazoan cells effectively eliminate intracellular protein aggregates3,4, indicating that efficient disaggregation and/or degradation mechanisms exist. However, metazoans lack the key heat-shock protein disaggregase HSP100 of non-metazoan HSP70-dependent protein disaggregation systems5,6, and the human HSP70 system alone, even with the crucial HSP110 nucleotide exchange factor, has p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
382
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(410 citation statements)
references
References 59 publications
(86 reference statements)
21
382
0
7
Order By: Relevance
“…Hsc70, notably, is the most abundant molecular chaperone in the motor neuron cytosol and is constitutively expressed, whereas Hsp70 proteins are at least fivefold less abundant. DnaJ proteins are also present at low levels relative to Hsc70, but, as observed recently, both the DnaJA and DnaJB class proteins play a cooperating role in disaggregation (7). Similarly, the three mammalian Hsp110 proteins (HspA4, HspA4L, and HspH1) are present at relatively low levels, but, as noted above, HspH1 was the only chaperone found to be induced in G85R mutant SOD1YFP-expressing motor neurons in vivo (3).…”
mentioning
confidence: 94%
“…Hsc70, notably, is the most abundant molecular chaperone in the motor neuron cytosol and is constitutively expressed, whereas Hsp70 proteins are at least fivefold less abundant. DnaJ proteins are also present at low levels relative to Hsc70, but, as observed recently, both the DnaJA and DnaJB class proteins play a cooperating role in disaggregation (7). Similarly, the three mammalian Hsp110 proteins (HspA4, HspA4L, and HspH1) are present at relatively low levels, but, as noted above, HspH1 was the only chaperone found to be induced in G85R mutant SOD1YFP-expressing motor neurons in vivo (3).…”
mentioning
confidence: 94%
“…Different eukaryotic J proteins produce varying effects on in vitro Hsp70 ATPase and refolding activities (32)(33)(34), or can act as holdases that prevent protein aggregation (35,36). Unique mixtures of J proteins can function as disaggregases (37,38). The function of the J proteins of mycobacteria has not been examined.…”
Section: Significancementioning
confidence: 99%
“…We purified Mtb Hsp20 (SI Appendix, Fig. S1B) and evaluated its ability to act as a sHsp with the heat denatured model substrate luciferase (24,38,57). Briefly, we heated luciferase at 42°C with and without excess Hsp20 for different times and monitored changes in solubility by ultracentrifugation to separate aggregated and native protein fractions, followed by Western blot analysis (13,58).…”
Section: Refolding Of a Model Aggregated Substrate By Mtb Chaperones Ismentioning
confidence: 99%
“…Recently, it was demonstrated that a complex of class A and B J-protein together with HSP-1 and HSP-110 is required for efficient protein disaggregation of amorphous protein aggregates. 87 Therefore, it would be interesting to analyze if either protein disaggregation of amorphous proteins is less efficient in the ER or if other complexes of chaperones are formed to compensate the lack of synergistic J-protein chaperone activity.…”
Section: Redox-regulation Of Chaperonesmentioning
confidence: 99%
“…88 As oxidative stress accompanies aging and neurodegenerative diseases, it has been speculated that the inactivation of this class of J-proteins may contribute to the increasing imbalance of proteostasis during aging and disease. 81 Other chaperone family members were also reported to harbor oxidative-sensitive cysteines, such as HSP-1 (e.g., protein folding and dissaggregation 87 ), CCT-4 (subunit of TCP/TriC complex, e.g. actin biogenesis 89 ) and CDC-48 (e.g., targeting of retro-translocated ERAD substrates 90 ).…”
Section: Redox-regulation Of Chaperonesmentioning
confidence: 99%